Dominância hierárquica, organização social e perfil de hidrocarbonetos cuticulares de Pachycondyla striata Fr. Smith, 1858 (Formicidae: Ponerinae) - Silva-Melo, Adolfo da [UNESP] (2014)
Early research on the importance of chemical compounds in social insect biology began in the twentieth century. In this period, researchers sought to understand the functional role(s) of cuticular hydrocarbons (HCs) in insect societies. Currently, HCs are implicated in the recognition of individuals within a colony, in determination of caste, gender, and species chemical profile, and for identification of social and reproductive status, which in the latter case is initially established through intra-colonial conflicts. Conflicts are conveniently viewed and understood via network visualization (i.e., graphs), and social network analyses are being widely used for this reason. With the help of this tool, we quantified agonistic interactions of Pachycondyla striata and evaluated dominance hierarchy structure using three indices of linearity (h, K and ttri). Our results indicate that this species has a linear dominance hierarchy, likely used to regulate colony division of reproductive labor. We also observed 16 behaviors performed in social conflict interactions. We used the GC-MS method to describe P. striata HCs, and we report the presence of chains on C19 - C31. The presence of a complex mixture of HCs with a chemical profile, unique to this species, highlights the possibility of chemotaxonomic identification, as well as distinction between populations and individuals